Israel : Technical Note on Crisis Prevention and Management. (IMF Staff Country Reports; Country Report ;, 2012)
This report analyzes the Israeli economy and its financial system in detail. A strong macroprudential framework is believed to be an effective tool in identifying in advance and extenuating threats that arise within the financial domain. It is also stated that the present fragile global economic environment is an important opportunity for Israeli authorities to safeguard and alter their financial rules as well as devise new frameworks to overcome the monetary crisis.